Competition, Regulation, and Performance in Television Broadcasting - John J. McGowan (Washington University Law Quarterly, 1967)
In this Article, Professor John McGowan provides a detailed description of the television industry's structure and the effects of competition on programming policy. McGowan offers ways in which FCC regulation of industry structure may promote diversity of programming without controlling the content of individual programs or broadcasters' programming policies.
Keywords: Communcations; Broadcasting; Federal regulation